Mobility aware‐Termite: a novel bio inspired routing protocol for mobile ad‐hoc networks. Issue 4 (1st December 2013) - Manjappa, Kiran; Guddeti, Ram Mohana Reddy
Abstract : In recent years, a lot of work has been done in an effort to incorporate swarm intelligence (SI) techniques in building an adaptive routing protocol for mobile ad‐hoc networks (MANETs). As centralised approach for routing in MANETs lack in scalability and fault‐tolerance, SI technique gives natural solutions through distributed approach to the adaptive routing for MANETs. The mobile nodes (MNs) found in existing MANETs are capable of monitoring the network status as well as data processing. Thus, the MANET can be made context aware with the help of MNs local monitoring capability. In the present work, a novel mobility aware bio inspired routing protocol for MANETs referred to as mobility aware‐Termite (MA‐Termite) is proposed. The objectives of the proposed protocol are twofold. (1) To find the reliable path based on the stable nodes in terms of its mobility with the help of the local monitoring capability of nodes. (2) To mitigate the measurement bias using pheromone smoothing. The proposed MA‐Termite is implemented in NS‐2 and the results are compared with other state‐of‐the‐art bio inspired and non‐bio inspired routing protocols for its evaluation. The MA‐Termite results are found to be convincing against its competing protocols in the carried out simulations.